Correspondence with Lord Hailey, former Governor of Punjab and U.P. - Khazan Singh; Singh, Manjeet, 1942- (Manjeet Singh, 1975)
Letters of a retired civil servant, 1947-1952, addressed to William Malcolm Hailey Hailey, baron on the 1947 communal disturbances in India and on corruption.